In vitro use of latency reversing agents to overcome HIV latency - Samer, Sadia [UNIFESP] (2017)
The use of antiretroviral therapy (ART) dramatically suppresses HIV replication to undetectable levels and can prolong the life of an infected individual, but low level viremia and proviral DNA are detected in majority of patients on ART even with intensifications of antiretroviral regimens. Furthermore virus typically rebounds within one to eight weeks once the treatment is interrupted. This rebound of viral load is mainly due to quiescent, integrated, replication competent latent proviral pool. Being latent, it remains hidden from the immune cells and the infection persists for years until and unless the cells carrying it die by apoptosis or are succumbed to cytopathic effect, once viral replication is induced by antigenic stimuli. Reducing this latent pool may help the patients to reach at least a transient drug-free remission of their disease. Latent HIV proviruses are silenced as a result of deacetylation and methylation of histones located at the long terminal repeats (LTRs) and lack of some viral (Tat) and host factors (NFKB, NFAT, AP1, PTEFb) that assist viral transcription. Breakthrough of latency reversal agents (LRAs) has helped to break this dormant HIV state so that HIV protein expression can be induced, followed by the clearance of that cell by viral cytopathic effects, immune cells among individuals under suppressive ART. Since HIV transcription is the interplay between host and viral factors, it utterly needs active cell state with upregulated transcription factors and their access to viral genome. We used two different approaches to activate the proviral compartment. One at chromatin level, Using Phytohaemagglutinin and histone deacetylase and methyltransferse inhibitors (HDACi and MTi, respectively) and the other approach was co-stimulation of the cells using Thalidomide coupled with Phytohaemagglutinin as TCR-agonist. Both ways were found efficient to reactivate/purge the virus from the patients on long term ART and undetectable viral load but the nature of the purged virus was different in both cases. The samples treated with HDACi/MTis were to be used later to sensitize monocyte derived dendritic cells (MDDCs) as MDDCs vaccine. So, we needed a high titer of virus. Viral purging was observed in samples of antiretroviral treated patients at different time points of supernatant collection, but the viral load showed decline over time in samples treated with HDACI/MTis (Nicotinamide and Chaetocin/BIX01294 respectively) in autologous culture. When cultures were shifted to an allogenic system to avoid host restriction factors, and to use healthy CD4 receptors to make new infection in order to obtain better viral yield, the virus behaved the same way, showing a viral load decline over time towards extinction. So the required viral titer could not be obtained due to massive misfit viral pool in the culture. Samples treated with Thalidomide showed an abrupt viral purging in 6/7 samples after 48 hours treatments with PHA and Thalidomide, in contrast to HDACi/MTis, where the average purging time was 5 days (Min 3, Max 7) and 6.5 days (Min 3, Max 29) respectively. Because the treatment with thalidomide was just for a mini in vitro test to check its latency reversal potential, we did not expand the virus from this treatment. We visually inspected the viral particles by electron microscopy, purged from both treatments. In first case where the samples were treated with HDACi/MTIs, we exclusively found virus with small size, diffused and unclear matrix and in most of cases lack of double membrane. In the second case where samples were treated with thalidomide, virus particles were of normal virus size, clear matrix and double membrane. We therefore hypothesize that long term suppressive ART will reduce the number of replicating competent HIV over time, since those strains will randomly interrupt latency and be eliminated by ART. This phenomenon might lead to the accumulation of defective HIV in proviral compartment. Finding of this cryptic defective provirus pool in autologous/allogenic system and defects seen by electron microscopy from the samples treated with HDACs/MTis and on the other hand normal viral population seen in the samples treated with a co-stimulator are directing to design new strategies aimed at eliminating cells harboring this defective proviral pool in order to further decrease the latent HIV reservoir among individuals under long term suppressive ART.